Enhanced Anti-melanoma Efficacy of a Pim-3-Targeting Bifunctional Small Hairpin RNA via Single-Stranded RNA-Mediated Activation of Plasmacytoid Dendritic Cells - Liu, Jing; Hu, Yuan; Guo, Qie; Yu, Xin; Shao, Liwei; Zhang, Cai (Frontiers in Immunology, 2019)
Melanoma is the most serious type of skin cancer. The immunosuppressive tumor microenvironment and aberrant expression of some proto-oncogenes are the main cause of melanoma development. We have constructed an ssRNA-Pim-3-shRNA dual-function vector, which activates the TLR7 to stimulate the anti-tumor immune response through ssRNA fragments, and simultaneously silences the proto-oncogene Pim-3 to intensify apoptosis of the tumor cells via shRNA. Here, we found that therapy with the ssRNA-Pim-3-shRNA dual-function vector not only promotes the apoptosis and inhibits the proliferation of B16F10 melanoma cells by inhibiting the express of Pim-3, but also enhances the activation of CD8+ T cells and NK cells and simultaneously reduces the proportion of intratumoral regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs). Together, these features effectively inhibit the growth of melanoma. Intriguingly, the bifunctional therapeutic effect that reverses the tumor immunosuppressive microenvironment is dependent on the activation of plasmacytoid dendritic cells (pDCs) and the secretion of type I IFN. Our study suggests that ssRNA-Pim-3-shRNA dual-function therapy is expected to become a promising therapeutic strategy for melanoma and other solid tumors with immunosuppressive microenvironment.